Bahasa Inggris - Dovel Pirmanto; Yora Haliza; Fahrel Yatul Firmansyah; Dedek Subhani (Yayasan Zia Salsabila, 2025)
The COVID-19 pandemic has impacted various aspects of life, including the education sector. The educational process at the State Islamic Institute (IAIN) Kerinci has also experienced quite significant changes, where the learning method has shifted from face-to-face to online learning. There is still not much research that discusses the correlation between the impact of Covid-19 and the mental and physiological health of students. This study aims to evaluate the impact of the pandemic on changes in the education system at IAIN Kerinci, with a particular focus on the challenges and opportunities that arise from the implementation of online learning. Through observation and questionnaires, this study involved lecturers and students to gain direct insight into the experiences and obstacles they face during the online learning process. The results of the study indicate that changes in education at IAIN Kerinci are faced with several problems, such as limited internet access, lack of digital skills, and low success rates in online learning. The world of education has changed rapidly due to the COVID-19 pandemic. This requires flexibility and innovation in the learning process despite the many challenges that must be faced. Further evaluation is needed to assess the effectiveness of online learning and the potential for sustainable development of educational technology at IAIN Kerinci.